2020
DOI: 10.1053/j.gastro.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis Subspecies cremoris Elicits Protection Against Metabolic Changes Induced by a Western-Style Diet

Abstract: A high sugar and high‐fat diet Western‐style diet can result in significant dyslipidemia, often leading to non‐alcoholic fatty liver disease (NAFLD), with females particularly affected by this diet irrespective of total caloric intake. Dietary supplementation with beneficial bacteria has been advocated as therapeutic intervention to modulate liver adiposity resulting from a Western‐style diet. Here, we assess the activity of beneficial bacteria on modulating the impact of a Western‐style diet in female mice. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 42 publications
7
33
1
Order By: Relevance
“…Recently, Naudin et al (2020) reported that Lactococcus lactis subsp. cremoris reduced high-fat-diet-caused weight gain, hepatic steatosis and inflammation as well as blood levels of cholesterol and glucose intolerance compared with LGG [ 87 ].…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…Recently, Naudin et al (2020) reported that Lactococcus lactis subsp. cremoris reduced high-fat-diet-caused weight gain, hepatic steatosis and inflammation as well as blood levels of cholesterol and glucose intolerance compared with LGG [ 87 ].…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…LGG High-fructose diet-fed mice ↑ Gut beneficial bacteria ↑ TJ-related protein expression ↓ Lipid accumulation ↓ ALT level [ 127] HFD-fed mice ↓ Fat content ↓ Serum TAG and cholesterol levels ↓ Liver inflammation [ 128] Bifidobacterium HFD-fed NAFLD rats ↓ Liver fat accumulation [ 129] NAFLD subjects ↓ Body weight and BMI ↓ TNF-level ↑ Serum antioxidant capacity [ 166] (Continued) HFD-fed mice ↓ Hepatic NKT cell depletion ↓ IR and hepatic steatosis [ 132] MCD-fed NASH mice ↓ Liver fibrosis [ 133] Lactococcus lactis subsp. cremoris Western diet-fed female mice ↓ Hepatic steatosis ↓ Liver fat inflammation ↓ IR and serum cholesterol level [ 134] Multistrain probiotic NAFLD patients ↓ NAS score ↓ Hepatic fibrosis ↓ Hepatocyte ballooning ↓ ALT and TNF-levels [ 135] Prebiotics Inulin-type fructans ApoE −/− mice fed a N-3 PUFA-depleted diet ↓ Hepatic inflammation ↑ GLP-1 and BA turnover [ 137] NASH patients ↓ ALT and AST levels [ 138] FOS MCD-fed NASH mice ↓ Hepatic steatosis ↓ Liver inflammation ↑ Gut barrier strength [ 140] IMOs HFD-fed NAFLD mice ↓ Weight gain ↓ IR and adiposity [ 141] Symbiotics Bifidobacterium longum with FOS NASH patients ↓ TNF-and serum LPS ↓ Hepatic steatosis ↓ NASH activity index [ 143] Seven probiotics and FOS NAFLD patients ↓ Hepatic steatosis ↓ Liver fibrosis ↓ ALT and AST levels [ 144] LBSF containing L. casei, L. rhamnosus, L. bulgari, B. longum, S. thermophilus, and FOS NASH patients ↓ ALT level ↓ Liver stiffness ↓ BMI and serum cholesterol [ 145] Lactobacillus reuteri with guar gum and inulin NASH patients ↓ Hepatic steatosis ↓ Weight gain [ 146] Arrows indicate an increase (↑) or decrease (↓) in the level of gene expression, protein activity, or phenotypic change. QHD, Qushi Huayu decoction; GC, geniposide and chlorogenic acid; DCHD, dachaihu decoction; WEGL, a water extract of Ganoderma lucidum mycelium; WD/VDD +/+ diet, westernized diet (high-fat/high-fructose corn syrup) deficient in vitamin D;…”
Section: Mastihamentioning
confidence: 99%
“…Cremoris, can effectively ameliorate liver inflammation and steatosis in western diet fed mice. [134] In addition, one randomized trial demonstrated that multi-strain probiotic (lactic acid bacteria and bifidobacteria) with exercise interventions can effectively alleviate NAFLD-related pathological phenotypes in biopsy-proven NAFLD patients. [135] Of note, apart from the benefits for liver diseases, our team recently investigated the role of two major probiotics (Lactobacillus casei LC122 and Bifidobacterium longum BL986) in anti-aging via regulation of the gut microbiota.…”
Section: Probiotics Prebiotics and Symbioticsmentioning
confidence: 99%
“…The probiotic Lactobacillus rhamnosus GG (LGG) increases beneficial bacteria in the distal small intestine, restores the intestinal barrier function, reduces liver inflammation and steatosis, and exerts protective effects on NAFL mice caused by high fructose diet[ 115 ]. However, the study by Naudin et al[ 116 ] found that in female mice on a high-fat, high-carbohydrate diet, dietary supplementation of Lactococcus lactis subspecies cremoris was more effective than dietary supplementation of LGG in reducing liver fat and inflammation development. In addition, a randomized clinical trial suggested that supplementation of VSL#3 for 4 mo can significantly improve NAFLD in children, and the mechanism may be the increase of glucagon-like peptide 1[ 117 ].…”
Section: Microbiota-gut-live-brain Axis and Nafldmentioning
confidence: 99%